Finance : a quantitative introduction. - Staszkiewicz, Piotr; Staszkiewicz, Lucia (Academic Press, an imprint of Elsevier, 2015)
Many students want an introduction to finance. Those who are quantitatively-oriented learners can benefit in particular from an introduction that puts more emphasis on mathematics and graphical presentations than on verbal descriptions. By illustrating core finance facts and concepts through equations and graphical material, this book can help people studying business management, marketing, accounting, and other subjects. Chapter-concluding questions (with answers) and case studies enhance its utility as a textbook and a reference. Its mixture of theory and problem-solving contains enough mathematical tools to help readers assess facts and evaluate real data in practical tasks. --